Penegakan Hukum terhadap Tindak Pidana Korupsi dalam Kasus Perdata di Wilayah Kota Kupang - Herlyn Anastacia; Deddy R Ch Manafe; Adrianus Djara Dima (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Law enforcement in civil cases that have obtained permanent legal force (inkracht van gewijsde) often faces various complex challenges. For example, in land ownership cases that may be suspected of being linked to corruption crimes. Therefore, law enforcement officials must ensure that there is strong and sufficient evidence to process criminal elements without undermining the legal certainty of civil cases that have been decided. Good coordination between civil and criminal judicial institutions is also essential to ensure that justice can be comprehensively upheld. This research is qualitative in nature regarding concepts, relevant laws, and legal facts related to the issues being studied. The data obtained is subsequently analyzed using descriptive analysis, which is an analysis conducted by elaborating the obtained data. The research results show that: (1) The procedure executed by law enforcement officials aligns with the legal authority granted to them. However, the process may result in losses for parties legally proven not to have committed unlawful acts, as evidenced by the final and binding legal decision, with the case dependent on further evidentiary proceedings; (2) Obstacles in law enforcement processes stem from three primary factors: the law itself, law enforcement officials, and society, wherein socio-political interventions can provoke public opinion and conflicts between law enforcement and the community.